IMPROVING THE STUDENTS’ SPEAKING SKILL BY USING MIND MAPPING TECHNIQUE AT UNIVERSITAS BINA DARMA - Ferry Kurniawan (Universitas PGRI Palembang, 2017)
The title of this study is improving the students’ speaking skill by using mind-mapping technique at Universitas BinaDarma. The problem of this study is: Is it effective to improve students’ speaking skill by using mind mapping technique? The purpose of this study is to know whether effective to use mind-mapping technique to improve the students’ speaking skill at Universitas BinaDarmaor not. The hypotheses of this study are: 1) H0. It is not significantly effective to improve the students speaking skill by using mind mapping technique. 2) Ha. It is significantly effective to improve the students’ speaking skill by using mind mapping technique. The method of this study was experimental method. Population of this study is Universitas BinaDarmastudents. Technique of colecting data was simple random sampling. result of this study is the null hypotheses was rejected.Keywords: Mind-mapping Technique, Speaking skill, Improve.